GC-MS chemical profiling, antioxidant, anti-diabetic, and anti-inflammatory activities of ethyl acetate fraction of Spilanthes filicaulis (Schumach. and Thonn.) C.D. Adams leaves: experimental and computational studies - Ojo, Oluwafemi Adeleke; Ogunlakin, Akingbolabo Daniel; Gyebi, Gideon Ampoma; Ayokunle, Damilare IyinKristi; Odugbemi, Adeshina Isaiah; Babatunde, Dare Ezekiel; Ajayi-Odoko, Omolola Adenike; Iyobhebhe, Matthew; Ezea, Samson Chukwuemeka; Akintayo, Christopher Oloruntoba; Ayeleso, Ademola; Ojo, Adebola Busola; et al. (Frontiers in Pharmacology, 2023)
This study aimed to investigate the chemical profile of GC-MS, antioxidant, anti-diabetic, and antiinflammatory activities of the ethyl acetate fraction of Spilanthes filicaulis leaves (EFSFL) via experimental and computational studies. After inducing oxidative damage with FeSO4, we treated the tissues with different concentrations of EFSFL. An in-vitro analysis of EFSFL was carried out to determine its potential for antioxidant, anti-diabetic, and anti-inflammatory activities. We also measured the levels of CAT, SOD, GSH, and MDA. EFSFL exhibited anti-inflammatory properties through membrane stabilizing properties (IC50 = 572.79 μg/mL), proteinase inhibition (IC50 = 319.90 μg/mL), and inhibition of protein denaturation (IC50 = 409.88 µg/mL). Furthermore, EFSFL inhibited α-amylase (IC50 = 169.77 µg/mL), α-glucosidase (IC50 = 293.12 µg/mL) and DPP-IV (IC50 = 380.94 µg/mL) activities, respectively. Our results indicated that induction of tissue damage reduced the levels of GSH, SOD, and CAT activities, and increased MDA levels. However, EFSFL treatment restores these levels to near normal. GC-MS profiling shows that EFSFL contains 13 compounds, with piperine being the most abundant. In silico interaction of the phytoconstituents using molecular and ensembled-based docking revealed strong binding tendencies of two hit compounds to DPP IV (alpha-caryophyllene and piperine with a binding affinity of -7.8 and -7.8 Kcal/mol), α-glucosidase (alpha-caryophyllene and piperine with a binding affinity of -9.6 and -8.9 Kcal/mol), and to α-amylase (piperine and Benzocycloheptano[2,3,4-I,j]isoquinoline, 4,5,6,6a-tetrahydro-1,9-dihydroxy-2,10-dimethoxy-5-methyl with a binding affinity of -7.8 and -7.9 Kcal/mol), respectively. These compounds also presented druggable properties with favorable ADMET. Conclusively, the antioxidant, antidiabetic, and anti-inflammatory activities of EFSFL could be due to the presence of secondary metabolites.